Chemical and Pharmacological Assessment of Substituted 1,2,4-Triazole Fused Pyrimidines as Anti-microbial Agent - Sabale, Prafulla; Potey, Lata; Waghmare, Suchita; Sayyad, Nusrat; Sabale, Vidya (Indian Journal of Pharmaceutical Education and Research, 2024)
Objectives: To synthesize a novel series of 3-(Aryl/Heteroaryl)-5-Methyl-7-Phenyl [1,2,4]triazolo[4,3a]Pyrimidines (5a-i). Materials and Methods: Synthesis was carried out though the microwave assisted synthesis, Spectroscopic approaches such as IR,1HNMR and MASS spectroscopy were used to characterize the produced substances. Antimicrobial screening was done by Cup Plate Method for the antibiotic zone determination and Minimum Inhibitory Concentration was determined by the tube dilution method. Experimental Work: The oxidation of substituted pyrimidinylhydrazones in dichloromethane with iodobenzene diacetate was used in the synthesis. Substituted pyrimidinylhydrazones was obtained by the condensation of 1-(1,4-dihydro-6-methyl-4-phenylpyrimidine-2-yl)-hydrazine containing a variety of aromatic/heteroaromatic aldehydes. 3-(Aryl/Heteroaryl)-5-Methy l-7-Phenyl-[1,2,4]triazolo[4,3a]Pyrimidines (5a-i) were investigated in vitro for antibacterial activity against gram-positive bacteria such as Bacillus subtilis and Staphylococcus aureus, as well as gram-negative bacteria such as Escherichia coli and Pseudomonas putida. Results: 3-(4-fluorophenyl)-5-Methyl-7-Phenyl-[1,2,4]Triazolo[4,3a]Pyrimidine (5a) and 3-(4-Nitrophenyl)-5-Methyl-7-Phenyl-[1,2,4]Triazolo[4,3a]Pyrimidine (5e) found effective when compared to known marketed drugs Streptomycin and Chloramphenicol as both compounds are having the substitution of most electronegative groups which shows strong interaction with targeted DNA Gyrase enzyme of the bacteria. Conclusion: Microwave found to be an eco-friendly method for cyclization of pyrimidinylhydrazone to triazolopyrimidine. This method was found to be clean, safe and operationally simple which give triazolopyrimidine products with high yield.
Keywords: Triazolopyrimidines; Pyrimidinylhydrazones; Iodobenzene diacetate; Antibacterial; activity